Liquid crystal polymer pellets, liquid crystal polymer powder, liquid crystal polymer film, and manufacturing method thereof
By using liquid crystal polymer pellets with a high orientation degree to produce films, the linear expansion coefficient in the plane is reduced, addressing the limitations of conventional films and enhancing the reliability of printed wiring boards.
Patent Information
- Application Number
- JP2023571395
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-05-27
- Filing Date
- 2023-05-22
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2043-05-22
AI Technical Summary
Conventional liquid crystal polymer films have a high linear expansion coefficient in the plane, which limits their dimensional stability and surface smoothness, making them less reliable for use in printed wiring boards.
The development of liquid crystal polymer pellets with an orientation degree of 86% or more, as measured by wide-angle X-ray scattering, which are then used to produce liquid crystal polymer films with a reduced in-plane linear expansion coefficient of 20 ppm/°C or less.
The resulting liquid crystal polymer films exhibit improved dimensional stability and surface smoothness, effectively reducing the linear expansion coefficient and enhancing the reliability of printed wiring boards.
Smart Images

Figure 0007673839000005 
Figure 0007673839000006 
Figure 0007673839000007
Abstract
Description
[Technical field]
[0001] The present invention relates to liquid crystal polymer pellets, a method for producing liquid crystal polymer pellets, a liquid crystal polymer powder, a method for producing a liquid crystal polymer powder, a liquid crystal polymer film, and a method for producing a liquid crystal polymer film. [Background technology]
[0002] In recent years, liquid crystal polymers (LCPs), which have less transmission loss and excellent high-frequency characteristics compared to conventional materials, have been attracting attention as a new substrate material for printed wiring compatible with next-generation high-speed transmission. Compared to polyimide resin, a conventional substrate material, LCPs have excellent low dielectric constant characteristics, high heat resistance, and low water absorption, which allows them to reduce loss of electrical signals, etc.
[0003] Known methods for producing LCP films from liquid crystal polymers for use in printed wiring boards and the like include, for example, melt extrusion and solution casting. The melt extrusion method is a method in which a film is formed by extruding molten resin from an apparatus and contacting it with a roll. The solution casting method is a method in which a varnish made by dissolving LCP raw materials such as LCP pellets in a solvent is applied onto a flat belt and dried to form an LCP film.
[0004] Meanwhile, Patent Document 1 describes a method for producing a fibril-like liquid crystal polymer powder. In this method, first, a biaxially oriented film of a liquid crystal polymer is pulverized to obtain a liquid crystal polymer (LCP) powder. Next, the obtained LCP powder is treated using a wet high-pressure crushing device to produce a fibril-like LCP powder. Such a fibril-like LCP powder can also be used as a raw material to produce an LCP film.
[0005] The most commonly used method for producing thermoplastic resin pellets is to extrude molten polymer through a nozzle provided at the discharge outlet into a string-like shape, pass the extruded polymer through a water bath to cool and solidify it, and then cut the resulting string-like material into pellets (the cold cut method) (see, for example, Patent Document 2 (JP Patent Publication 1998-180753 A)). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5904307 [Patent Document 2] Japanese Patent Application Publication No. 10-180753 Summary of the Invention [Problem to be solved by the invention]
[0007] When a liquid crystal polymer film is used as a substrate for printed wiring, for example, it is desirable that the film has high surface smoothness (flatness) and high dimensional stability (small in-plane linear expansion coefficient) in order to improve the reliability of the printed wiring. Here, conventional liquid crystal polymer films have room for further improvement in terms of reducing the in-plane linear expansion coefficient. Therefore, it was decided to increase the degree of orientation of the liquid crystal polymer pellets used as the raw material and reduce the in-plane linear expansion coefficient.
[0008] In view of the above problems, the present invention provides a liquid crystal polymer film having a small in-plane linear expansion coefficient. Obtaining liquid crystal polymer pellets for The purpose of this document is to: [Means for solving the problem]
[0009] A liquid crystal polymer pellet according to a first aspect of the present invention contains a liquid crystal polymer and is used as a material for a liquid crystal polymer film. The liquid crystal polymer pellet has a degree of orientation of 86% or more as measured by wide-angle X-ray scattering.
[0010] A method for producing a liquid crystal polymer powder according to a second aspect of the present invention includes the steps of: a fine pulverizing step of pulverizing the liquid crystal polymer pellets in a state of being dispersed in liquid nitrogen to obtain granular finely pulverized liquid crystal polymer; The method further includes a fiberization step in which the finely pulverized liquid crystal polymer is crushed in a wet high-pressure crushing device to obtain a liquid crystal polymer powder.
[0011] A liquid crystal polymer film according to a third aspect of the present invention includes a liquid crystal polymer, and the liquid crystal polymer film has an in-plane linear expansion coefficient of 20 ppm / ° C. or less. Effect of the Invention
[0012] According to the present invention, the in-plane linear expansion coefficient of the liquid crystal polymer film is reduced. Obtaining liquid crystal polymer pellets for It is possible. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a diagram showing the relationship between the degree of orientation of liquid crystal polymer pellets and the coefficient of linear expansion (CTE) of liquid crystal polymer films in Examples and Comparative Examples. [Diagram 2] FIG. 2 is a diagram showing the relationship between the orientation degree and packed bulk density of liquid crystal polymer pellets in Examples and Comparative Examples. [Diagram 3] 2 is a photograph of the liquid crystal polymer pellets in Example 1. [Figure 4] 2 is a photograph of liquid crystal polymer pellets in Comparative Example 1. [Diagram 5] 3 is a photograph of liquid crystal polymer pellets in Comparative Example 2. [Figure 6] 3 is a photograph of liquid crystal polymer pellets in Example 2. [Figure 7] 1 is a photograph of liquid crystal polymer pellets in Example 3. [Figure 8] 1 is a photograph of liquid crystal polymer pellets in Example 4. [Figure 9] FIG. 2 is a flow diagram showing a manufacturing process of a liquid crystal polymer pellet according to an embodiment. [Figure 10] FIG. 2 is a flow diagram showing a manufacturing process of a liquid crystal polymer powder according to an embodiment. [Figure 11] FIG. 2 is a flow diagram showing a manufacturing process of the liquid crystal polymer film of the embodiment. [Figure 12] 1 is a graph showing the relationship between the take-up speed in Reference Test 1 and the packed bulk density of the LCP pellets, the degree of orientation of the LCP pellets, and the CTE of the LCP film. [Figure 13] 1 is a graph showing the relationship between the melting temperature in Reference Test 2 and the packed bulk density of the LCP pellets, the degree of orientation of the LCP pellets, and the CTE of the LCP film. [Figure 14] FIG. 2 is a flow diagram showing a manufacturing process of a fiber mat according to an embodiment. [Figure 15] FIG. 2 is a diagram showing a matting step for matting liquid crystal polymer powder in the process for producing a fiber mat. [Figure 16] FIG. 13 is a diagram showing a process of irradiating a second surface of the fiber mat with light. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these.
[0015] <Liquid crystal polymer pellets> The liquid crystal polymer (LCP) pellets according to the present embodiment contain a liquid crystal polymer and are used as a material for a liquid crystal polymer film. The liquid crystal polymer pellets have an orientation degree of 86% or more as measured by wide angle X-ray scattering (WAXS).
[0016] Wide-angle X-ray scattering (WAXS) analysis is a measurement technique that observes the scattered X-rays generated when a sample is irradiated with X-rays, and can be used to calculate the crystal structure and degree of orientation of polymers (the percentage of molecular chains that are aligned). In this embodiment, the WAXS analysis is performed using a wide-angle measurement mode of a small-angle X-ray scattering analyzer ("NANOPIX" manufactured by Rigaku). The distance between the sample and the detector is 80 mm, and the distance is calibrated using Si. The sample is irradiated with X-rays and the scattered X-rays are detected by the detector in a vacuum environment. A beam stopper is placed between the sample and the detector to block a portion of the scattered X-rays from reaching the detector. X-rays are irradiated at an angle of 80° to 100° with respect to the cut cross section of the pellet. The degree of orientation is calculated from the circular integral at the strongest peak of the scattering intensity of the scattered X-rays.
[0017] The packed bulk density of the liquid crystal polymer pellets is preferably 0.3 g / cm 3 More preferably, it is 0.09 to 0.35 g / cm 3 In this case, the liquid crystal polymer pellets can be easily pulverized.
[0018] In measuring the packed bulk density, first, LCP pellets are filled into a measuring cylinder (maximum scale: 100 mL) up to the 100 mL mark, and the weight of the filled LCP pellets is measured. Then, tapping (up and down vibration of the measuring cylinder) is performed 10 times, and the volume of the LCP pellets after tapping is confirmed by the scale of the measuring cylinder. The packed bulk density is calculated from the following formula. Packed bulk density (g / cm 3 ) = [Weight of filled LCP pellets (g)] / [Volume of LCP pellets after tapping (cm 3 )〕
[0019] The liquid crystal polymer pellets preferably have fibrous branched portions such as burrs, fluff, etc. When the liquid crystal polymer pellets have fibrous branched portions, the liquid crystal polymer pellets can be pulverized in a short time by low-temperature pulverization.
[0020] The liquid crystal polymer is, for example, a thermotropic liquid crystal polymer. The molecules of the liquid crystal polymer have a negative linear expansion coefficient (coefficient of thermal expansion: CTE) in the axial direction of the molecular axis, and a positive CTE in the radial direction of the molecular axis. It is preferable that the liquid crystal polymer does not have an amide bond.
[0021] Examples of thermotropic liquid crystal polymers that do not have amide bonds include copolymers of parahydroxybenzoic acid, terephthalic acid, and dihydroxybiphenyl (block copolymers of parahydroxybenzoic acid and ethylene terephthalate) that have a high melting point and a low CTE and are called type 1 liquid crystal polymers, and copolymers (block copolymers) of parahydroxybenzoic acid and 2,6-hydroxynaphthoic acid that have a melting point between type 1 liquid crystal polymers and type 2 liquid crystal polymers and are called type 1.5 (or type 3) liquid crystal polymers.
[0022] The melting point of the liquid crystal polymer is preferably higher than 280° C., and more preferably higher than 300° C. The "melting point" here means the "endothermic peak temperature" measured using a differential scanning calorimeter while heating the LCP to 400° C. in an inert atmosphere, cooling it to room temperature at a temperature drop rate of 40° C. / min or more, and then heating it again at a temperature increase rate of 40° C. / min. When the melting point (endothermic peak temperature) of the LCP exceeds 300° C., an LCP film with excellent heat resistance can be obtained.
[0023] From the viewpoint of forming an LCP film, the melting point of the liquid crystal polymer is preferably lower than the decomposition temperature of LCP, for example, 400° C. or lower.
[0024] The melt viscosity of the liquid crystal polymer is preferably 15 to 79 Pa·s, which can further improve the in-plane CTE of the LCP film.
[0025] The melt viscosity of the liquid crystal polymer is measured by a Capillograph manufactured by Toyo Seiki Seisakusho Co., Ltd. under the following measurement conditions in accordance with JIS K7199. Temperature: (Melting point + 25℃) Shear rate: 1000 sec -1 Capillary: Length 20mm / Diameter 1mm
[0026] <Method of manufacturing liquid crystal polymer pellets> Hereinafter, a method for producing liquid crystal polymer pellets according to one embodiment of the present invention will be described.
[0027] As shown in FIG. 9, the method for producing liquid crystal polymer pellets according to this embodiment includes a melt-kneading step (S01), an extruding step (S02), a cooling step (S03), and a cutting step (S04) in this order.
[0028] (Melting and kneading process: S01) In the melt-kneading step, the liquid crystal polymer raw material is kneaded while being heated and melted. The melt-kneading step can be carried out, for example, by using a co-rotating twin-screw extruder. Kneading is carried out, for example, by a screw (such as a co-rotating twin-screw extruder). The heating temperature (melting temperature) is preferably equal to or higher than the melting point of the LCP raw material. If the melting temperature is lower than the melting point of the LCP raw material, the degree of orientation of the LCP pellets tends to decrease.
[0029] (Extrusion process: S02) In the extrusion process, the liquid crystal polymer raw material after the melt-kneading process is extruded into a string shape. Specifically, for example, the liquid crystal polymer raw material is extruded toward the nozzle while being kneaded by the rotation of the screw, and the string-shaped liquid crystal polymer (string-shaped object) is extruded from the nozzle hole.
[0030] (Cooling process: S03) In the cooling step, the string-like material obtained in the extrusion step is cooled in water while being taken up.
[0031] Here, the ratio [V / Q] of the extrusion amount Q (kg / h) of the string-like material in the extrusion process to the take-up speed V (m / min) of the string-like material in the cooling process is 5 to 20. When this ratio (draw ratio) [V / Q] is 5 or more, it is possible to obtain LCP pellets with an orientation degree of 86% or more. If V / Q exceeds 20, the string-like material may be cut by taking it up, which may make production difficult.
[0032] The extrusion rate (the same rate as the supply rate of the LCP raw material) is preferably 2 to 20 kg / h, more preferably 2 to 10 kg / h. The take-up speed of the string-like material in the cooling step is preferably 4 to 70 m / min, more preferably 20 to 60 m / min.
[0033] (Cutting process: S04) In the cutting step, the string-like material after the cooling step is cut.
[0034] Through the above steps, the liquid crystal polymer pellets of the present embodiment can be obtained.
[0035] <Liquid crystal polymer powder> A liquid crystal polymer (LCP) powder according to one embodiment of the present invention contains fibrous particles made of a liquid crystal polymer.
[0036] (fibrous particles) The fibrous particles contained in the LCP powder are not particularly limited as long as they contain a fibrous portion. The fibrous portion may be linear or may have branches.
[0037] The average aspect ratio of the fibrous particles is preferably 10 or more and 500 or less, more preferably 300 or less, and even more preferably 100 or less. The average diameter of the fibrous particles is more preferably 2 μm or less, and more preferably 1 μm or less. Such an LCP powder containing fine fibrous particles cannot be produced by a conventional method. For example, ultrafine fibers made of LCP obtained by cutting continuous LCP long fibers produced by a conventional electrospinning method usually have an aspect ratio of more than 500.
[0038] The average diameter and average aspect ratio of the fibrous particles contained in the LCP powder are measured by the following method.
[0039] (Measurement of the average diameter and average aspect ratio of fibrous particles) The LCP powder to be measured is dispersed in ethanol to prepare a slurry containing 0.01% by mass of LCP powder. At this time, the slurry is prepared so that the water content in the slurry is 1% by mass or less. Then, 5 to 10 μL of this slurry is dropped onto a slide glass, and the slurry on the slide glass is allowed to dry naturally. By allowing the slurry to dry naturally, the LCP powder is placed on the slide glass. Next, a predetermined area of the LCP powder placed on the slide glass is observed with a scanning electron microscope to collect 100 or more pieces of image data of the particles constituting the LCP powder. In collecting the image data, the area is set according to the size of each LCP particle so that the number of image data is 100 or more. In order to prevent the occurrence of missed image data collection or measurement errors for each particle of the LCP, the magnification of the scanning electron microscope is appropriately changed to 500x, 3000x, or 10000x to collect the image data. Next, using the collected image data, the longitudinal dimension and width dimension of each particle of the LCP powder are measured. The direction of the straight line connecting both ends of the longest path among the paths that can be taken on one particle of the LCP powder captured in each of the image data, i.e., the path that passes through approximately the center of the particle from one end to the opposite end of the particle, is defined as the longitudinal direction. The length of the straight line connecting both ends of the longest path is measured as the longitudinal dimension. In addition, the particle size in the direction perpendicular to the longitudinal direction is measured at three different points in the longitudinal direction of each particle of the LCP powder, and the average value of the dimensions measured at these three points is defined as the width direction dimension (fiber diameter) per particle of the LCP powder. Furthermore, the ratio of the longitudinal dimension to the fiber diameter [longitudinal dimension / fiber diameter] is calculated to obtain the aspect ratio of the fibrous particle. The average value of the fiber diameters measured for 100 fibrous particles is taken as the average diameter. The average aspect ratio is determined as the average value of the aspect ratios measured for 100 fibrous particles.
[0040] The fibrous particles may be contained in the LCP powder as aggregates of the fibrous particles.
[0041] In addition, the axial direction of the LCP molecules constituting the fibrous particles tends to coincide with the longitudinal direction of the fibrous particles. When an LCP powder is produced through a fiberization process described below, it is believed that the axial direction of the LCP molecules is aligned along the longitudinal direction of the fibrous particles due to breakage between multiple domains formed by bundling the LCP molecules.
[0042] The bulk density of the LCP powder is preferably 2 to 5 mg / cm. 3 It is.
[0043] In the LCP powder, the content (number ratio) of particles other than fibrous particles (aggregated particles that are not substantially fibrous) is preferably 20% or less. For example, when the LCP powder is placed on a flat surface, particles with a maximum height of 10 μm or less are fibrous particles, and particles with a maximum height of more than 10 μm are aggregate particles.
[0044] The LCP powder preferably has a D50 (average particle size) value of 13 μm or less, as measured by particle size measurement using a particle size distribution measuring device based on a laser diffraction scattering method.
[0045] The liquid crystal polymer powder may further contain a zirconium compound. The zirconium compound is preferably contained in an amount of 0.001% by weight or more and 0.1% by weight or less, more preferably 0.003% by weight or more and 0.05% by weight or less, based on the total amount of the liquid crystal polymer powder. By containing a small amount of zirconium compound, when light is irradiated in a subsequent processing step, the light irradiation efficiency can be increased due to the light absorption characteristics of the zirconium compound.
[0046] The zirconium compound refers to a compound containing a zirconium atom. Examples of the zirconium compound include zirconium acetate, zirconium hydroxide, and zirconium oxide, and among them, zirconium dioxide (zirconia) is preferably used. The zirconium compound contained in the liquid crystal polymer powder is preferably particulate, and the particle size is preferably 1 nm or more and 500 μm or less, more preferably 10 nm or more and 100 nm or less. It is assumed that the zirconium compound is mixed with the one used as a medium when crushing the coarsely crushed liquid crystal polymer during the manufacturing process of the liquid crystal polymer powder.
[0047] <Liquid crystal polymer film> A liquid crystal polymer (LCP) film according to one embodiment of the present invention comprises a liquid crystal polymer.
[0048] The coefficient of linear expansion (CTE) of the LCP film in the plane (XY directions) is preferably 20 ppm / °C or less, and more preferably 18 to 20 ppm / °C. The linear expansion coefficient of the LCP film is the in-plane (XY direction) linear expansion coefficient of the LCP film measured by the TMA (thermomechanical analysis) method in accordance with JIS K 7197. The conditions of the TMA method are heating from room temperature to 150°C at 10°C / min in a nitrogen atmosphere, a load of 10 g, and a rectangular sample shape (5 mm x 15 mm).
[0049] Thus, an LCP film having an in-plane CTE of 20 ppm / ° C. or less can be suitably used as a substrate for a flexible printed circuit (FPC), a diaphragm, an organic semiconductor substrate, an organic EL substrate, a vibration damper, etc. In other words, from the viewpoint of being applicable to the above-mentioned substrates, etc., it is preferable that the LCP film according to this embodiment has a small in-plane linear expansion coefficient.
[0050] The thickness of the LCP film is preferably, for example, 5 μm or more and 250 μm or less.
[0051] The LCP film preferably has a water absorption rate of 0.2% by mass or less when immersed in water at room temperature for 24 hours. Thus, if the water absorption rate is 0.2% by mass or less, the LCP film can be more suitably used as a high-frequency circuit board member. If an LCP film having a water absorption rate of 0.2% by mass or less is used as a high-frequency circuit board member, the high-frequency circuit board is prevented from containing water with an extremely high dielectric constant, and an increase in dielectric loss due to an increase in the relative dielectric constant and dielectric loss tangent can be suppressed, and further, the occurrence of inconsistency in characteristic impedance due to a change in the dielectric constant and the associated transmission loss can be suppressed. For example, an LCP film made of a liquid crystal polymer having an amine-derived structure introduced into its molecular structure has a relatively high water absorption rate, and therefore has a water absorption rate of more than 0.2% by mass.
[0052] The LCP film according to the present embodiment may have copper foil bonded to at least one surface, or may have copper foil bonded to both surfaces. In this case, the LCP film according to the present embodiment may be used as a laminated molded product, for example, as FCCL (Flexible Copper Clad Laminates) that allows circuit formation by a subtractive method.
[0053] <Fiber mat> The fiber mat according to one embodiment of the present invention includes a liquid crystal polymer. The breaking tension of the fiber mat of this embodiment is preferably 1.0 N / 20 mm or more, more preferably 1.2 N / 20 mm or more. The breaking tension of the fiber mat may be 1.5 N / 20 mm or more, or may be 1.8 N / 20 mm or more. According to the present invention, even when the heat treatment is performed at a temperature below the melting point of the liquid crystal polymer, the breaking tension can be improved compared to the fiber mat before the heat treatment, and a fiber mat having a breaking tension of 1.0 N / 20 mm or more can be obtained.
[0054] The breaking tension of the fiber mat can be measured using an autograph (AG-XDplus manufactured by Shimadzu Corporation). In this case, the width of the fiber mat at the time of measurement is 20 mm.
[0055] The overall basis weight of the fiber mat is approximately 30-40 g / m 2 The overall density of the fiber mat is, for example, 0.30 to 0.60 g / m 3 and the density increases as the fused area of the liquid crystal powder polymer in the thickness direction increases.
[0056] The thickness of the fiber mat is approximately 50 to 100 μm, and the thickness decreases as the fused region of the liquid crystal powder polymer in the thickness direction becomes larger.
[0057] <<Methods of manufacturing liquid crystal polymer powder, liquid crystal polymer film and fiber mat>> Hereinafter, a method for producing a liquid crystal polymer powder and a liquid crystal polymer film according to one embodiment of the present invention will be described.
[0058] <Method of manufacturing liquid crystal polymer powder> As shown in FIG. 10, the method for producing a liquid crystal polymer powder according to this embodiment includes, in this order, a coarse pulverization step (S11), a fine pulverization step (S12), a coarse particle removal step (S13), and a fiberization step (S14).
[0059] (Coarse grinding process: S11) In the coarse pulverization step, the LCP pellets are coarsely pulverized. For example, the LCP pellets are coarsely pulverized with a cutter mill. The size of the coarsely pulverized LCP particles is not particularly limited as long as they can be used as a raw material for the fine pulverization step described later. The maximum particle size of the coarsely pulverized LCP particles is, for example, 3 mm or less.
[0060] The method for producing an LCP film in this embodiment does not necessarily have to include a coarse pulverization step. For example, if the LCP pellets can be used as a raw material for the fine pulverization step, the LCP pellets may be directly used as a raw material for the fine pulverization step. In the coarse pulverization step, it is preferable to perform coarse pulverization in a high-pressure dispersed state. The number of dispersion treatments is preferably 1 to 50 times, more preferably 1 to 10 times. By performing pulverization by high-pressure dispersion in the coarse pulverization step, it becomes easier to obtain a granular finely pulverized liquid crystal polymer in a subsequent step.
[0061] (Fine grinding process: S12) In the fine pulverization step, the LCP pellets (after the coarse pulverization step) are dispersed in liquid nitrogen and pulverized to obtain granular finely pulverized liquid crystal polymer (finely pulverized LCP).
[0062] In the pulverization step, it is preferable to pulverize the LCP pellets dispersed in liquid nitrogen using media. The media is, for example, beads. For example, zirconia particles can be used as the media. The particle size of the zirconia used as the media is preferably 0.1 mm or more and 10 mm or less, more preferably 1 mm or more and 8 mm or less. In the pulverization step of this embodiment, it is preferable to use a bead mill, which has relatively few technical problems, from the viewpoint of handling liquid nitrogen. An example of a device that can be used in the pulverization step is the liquid nitrogen bead mill "LNM-08" manufactured by Imex.
[0063] In the fine pulverization process of this embodiment, the pulverization method of pulverizing the liquid crystal polymer in a state of being dispersed in liquid nitrogen is different from the conventional freeze pulverization method. The conventional freeze pulverization method is a method of pulverizing the raw material to be pulverized while pouring liquid nitrogen onto the raw material to be pulverized and the main body of the pulverization device, but most of the liquid nitrogen has evaporated at the time the raw material to be pulverized is pulverized. In other words, in the conventional freeze pulverization method, most of the raw material to be pulverized is not dispersed in liquid nitrogen at the time the raw material to be pulverized is pulverized.
[0064] In the conventional freeze-pulverization method, the heat of the raw material to be pulverized itself, the heat generated by the pulverization device, and the heat generated by the pulverization of the raw material to be pulverized vaporize the liquid nitrogen in an extremely short time. Therefore, in the conventional freeze-pulverization method, the raw material being pulverized inside the pulverization device is at a temperature much higher than the boiling point of liquid nitrogen, which is -196°C. In other words, in the conventional freeze-pulverization method, pulverization is performed under conditions where the temperature inside the pulverization device is usually between -100°C and 0°C. In the conventional freeze-pulverization method, even if as much liquid nitrogen as possible is supplied, the temperature inside the pulverization device is at its lowest about -150°C.
[0065] For this reason, when, for example, a uniaxially oriented pellet-shaped liquid crystal polymer (or a coarsely pulverized product thereof) is pulverized in the conventional freeze-pulverization method, the pulverization proceeds along a plane approximately parallel to the axial direction of the molecular axis of the liquid crystal polymer, and it is considered that a fibrous liquid crystal polymer having a very large aspect ratio and a fiber diameter far larger than 3 μm is obtained. In other words, even if a uniaxially oriented pellet-shaped liquid crystal polymer is pulverized by the conventional freeze-pulverization method, it is not possible to obtain a granular finely pulverized liquid crystal polymer as used in this embodiment.
[0066] In this embodiment, the raw material to be pulverized is pulverized in a state dispersed in liquid nitrogen, so that the raw material is pulverized in a state that is even more cooled than in the conventional freeze-pulverization method. Specifically, the raw material to be pulverized is pulverized at a temperature lower than −196° C., which is the boiling point of liquid nitrogen. When the raw material to be pulverized at a temperature lower than −196° C. is pulverized, the raw material to be pulverized is pulverized by repeating brittle fracture of the raw material to be pulverized. As a result, even when a uniaxially oriented liquid crystal polymer is pulverized, for example, not only does the fracture progress on a plane approximately parallel to the axial direction of the molecular axis of the liquid crystal polymer, but also brittle fracture progresses along a plane intersecting the axial direction, so that a granular pulverized LCP can be obtained.
[0067] In the freeze-pulverization method of the present embodiment, the rotation speed of the freeze-pulverization is preferably 1800 rpm or more, more preferably 2000 rpm or more, and even more preferably 2500 rpm or more. By adopting such a rotation speed, it becomes easier to obtain a granular finely pulverized liquid crystal polymer having a desired aspect ratio.
[0068] In the pulverization step of this embodiment, the liquid crystal polymer, which has been granulated by brittle fracture in liquid nitrogen, is continuously subjected to impact with a medium or the like while in an embrittled state, so that a plurality of fine cracks are formed from the outer surface to the inside of the liquid crystal polymer obtained in the pulverization step of this embodiment.
[0069] The granular finely pulverized LCP obtained by the fine pulverization process preferably has a D50 of 50 μm or less as measured by a particle size distribution measuring device using a laser diffraction scattering method, which can prevent the granular finely pulverized LCP from clogging the nozzle in the fiberization process described below.
[0070] (Coarse particle removal process: S13) Next, in the coarse particle removal step, coarse particles are removed from the granular pulverized LCP obtained in the pulverization step. For example, the granular pulverized LCP is sieved through a mesh to obtain granular pulverized LCP that falls below the sieve, and the granular pulverized LCP that falls above the sieve is removed to remove the coarse particles contained in the granular pulverized LCP. The type of mesh may be appropriately selected, and examples of the mesh include meshes with an opening of 53 μm. The method for producing a liquid crystal polymer powder according to this embodiment does not necessarily have to include the coarse particle removal step.
[0071] (Fiberization process: S14) Next, in the fiberization process, the granular pulverized LCP is crushed by a wet high-pressure crushing device to obtain a liquid crystal polymer powder. In the fiberization process, the pulverized LCP is first dispersed in a dispersion medium for the fiberization process. The pulverized LCP to be dispersed does not need to have coarse particles removed, but it is preferable that the coarse particles have been removed. Examples of the dispersion medium for the fiberization process include water, ethanol, methanol, isopropyl alcohol, toluene, benzene, xylene, phenol, acetone, methyl ethyl ketone, diethyl ether, dimethyl ether, hexane, or a mixture thereof.
[0072] Then, the finely pulverized LCP dispersed in the dispersion medium for the fiberization process, i.e., the finely pulverized LCP in a paste or slurry state, is passed through the nozzle under high pressure. By passing through the nozzle at high pressure, the shear force or collision energy due to the high-speed flow in the nozzle acts on the liquid crystal polymer, and the granular finely pulverized LCP is crushed, so that the fiberization of the liquid crystal polymer progresses, and a liquid crystal polymer powder that can be used in the manufacturing method of a liquid crystal polymer film can be obtained. From the viewpoint of applying a high shear force or high collision energy, it is preferable that the nozzle diameter of the nozzle is as small as possible within a range in which the finely pulverized LCP does not clog the nozzle. Since the particle diameter of the granular finely pulverized LCP in this embodiment is relatively small, the nozzle diameter in the wet high-pressure crushing device used in the fiberization process can be made small. The nozzle diameter is, for example, 0.2 mm or less.
[0073] In this embodiment, as described above, a plurality of fine cracks are formed in the granular pulverized LCP. Therefore, the dispersion medium penetrates into the inside of the pulverized LCP through the fine cracks by pressurization in the wet high-pressure crushing device. Then, when the paste-like or slurry-like pulverized LCP passes through the nozzle and is placed under normal pressure, the dispersion medium that penetrates into the inside of the pulverized LCP expands in a short time. The dispersion medium that penetrates into the inside of the pulverized LCP expands, and destruction proceeds from the inside of the pulverized LCP. Therefore, fiberization proceeds to the inside of the pulverized LCP, and the liquid crystal polymer molecules are separated into domain units in which they are aligned in one direction. Thus, in the fiberization process in this embodiment, by defibrating the granular pulverized LCP obtained in the fine grinding process in this embodiment, a liquid crystal polymer powder having a lower content of aggregated particles and a fine fibrous form can be obtained, compared to the liquid crystal polymer powder obtained by crushing the granular liquid crystal polymer obtained by the conventional freeze grinding method.
[0074] In the fiberization process in this embodiment, the finely pulverized LCP may be crushed by a wet high-pressure crushing device multiple times to obtain liquid crystal polymer powder. It is preferable that the number of times of crushing by the wet high-pressure crushing device is small. The number of times of crushing by the wet high-pressure crushing device may be, for example, 5 times or less.
[0075] <Method of manufacturing liquid crystal polymer film> As shown in FIG. 11, the method for producing a liquid crystal polymer film according to this embodiment includes a dispersing step (S21), a matting step (S22), a hot pressing step (S23), and a metal foil removing step (S24).
[0076] (Dispersion process: S21) In the dispersion step, which is the first step of the method for producing a liquid crystal polymer film, the liquid crystal polymer powder is dispersed in a dispersion medium to form a paste or slurry. In this manner, in this embodiment, the liquid crystal polymer powder in the form of fine fibers is used, so that the liquid crystal polymer powder can be dispersed in a dispersion medium with high viscosity. As a result, a homogeneous liquid crystal polymer film can be produced.
[0077] The dispersion medium used in the dispersion step includes water, terpineol, ethanol, and mixtures thereof. For example, when terpineol is used as the dispersion medium, a paste-like liquid crystal polymer powder is obtained. When a mixture of ethanol and water is used as the dispersion medium, a slurry-like liquid crystal polymer is obtained.
[0078] (Matting process: S22) Next, in the matting step, the liquid crystal polymer powder in the paste or slurry form is dried to form a liquid crystal polymer fiber mat. In one embodiment of the present invention, the matting step includes, for example, a coating step and a drying step.
[0079] In the coating process, the liquid crystal polymer powder paste is applied to a metal foil such as a copper foil. In the coating process, the liquid crystal polymer powder paste is applied to a metal foil such as a copper foil as described above, but instead of the metal foil, a polyimide film, a PTFE (polytetrafluoroethylene) film, or a composite sheet made of a reinforcing material such as a glass fiber fabric and a heat-resistant resin may be used. This makes it easy to industrially produce the liquid crystal polymer film.
[0080] Next, in a drying step, the paste-like liquid crystal polymer applied to the copper foil is heated and dried to evaporate the dispersion medium. The dispersion medium may be evaporated by suction. By the above heating and drying, a liquid crystal polymer fiber mat is formed on the metal foil such as the copper foil.
[0081] In addition, in the drying process, the dispersion medium is gradually removed from the paste-like liquid crystal polymer powder, so the overall thickness of the paste-like liquid crystal polymer powder gradually becomes thinner during drying. Therefore, the thickness of the liquid crystal polymer fiber mat becomes thinner than the overall thickness of the paste-like liquid crystal polymer formed on the copper foil. Specifically, in this embodiment, the overall thickness of the paste-like liquid crystal polymer powder is about 700 μm, and the thickness of the liquid crystal polymer fiber mat is, for example, about 150 μm.
[0082] Furthermore, as the overall thickness of the paste-like LCP powder gradually decreases during drying, the longitudinal direction of the fibrous particles in the LCP powder changes. Specifically, among the fibrous particles, those having a longitudinal direction along the overall thickness direction of the paste-like liquid crystal polymer powder tilt so that their longitudinal direction faces the in-plane direction of the copper foil. Therefore, the longitudinal direction of the fibrous particles in the formed liquid crystal polymer fiber mat is anisotropic.
[0083] In the matting step, a liquid crystal polymer paste may be applied to the liquid crystal polymer fiber mat formed on the metal foil by the drying step, and then the paste may be dried to evaporate the dispersion medium. In this manner, the matting step may include a coating step and a drying step repeated in this order. This allows a liquid crystal polymer fiber mat having a desired basis weight to be obtained.
[0084] The liquid crystal polymer fiber mat in this embodiment is formed by entangling fibrous particles of the liquid crystal polymer powder with each other. The liquid crystal polymer fiber mat has voids between the liquid crystal polymer powder particles. As described above, the longitudinal direction of the fibrous particles in the liquid crystal polymer powder is generally inclined toward the in-plane direction of the copper foil, so that the void ratio of the liquid crystal polymer fiber mat tends to be larger than that of a liquid crystal polymer mat obtained by matting a conventional liquid crystal polymer powder that does not contain fibrous particles. The void ratio is, for example, 80% to 90%.
[0085] In the matting process in this embodiment, instead of the coating process and drying process, a liquid crystal polymer powder in a paste or slurry form may be formed into a liquid crystal polymer fiber mat by a papermaking method. According to the papermaking method, it is not necessary to use a special dispersion medium (e.g., expensive terpineol) used in the coating process. In addition, in the papermaking method, the dispersion medium used in the dispersion process can be recovered and reused. In this way, the liquid crystal polymer film can be produced at low cost by the papermaking method.
[0086] In the mat-making process using the papermaking method, specifically, first, a liquid crystal polymer powder in a paste or slurry form is papered onto a mesh, a nonwoven microporous sheet, or a woven fabric, and then the liquid crystal polymer paste or slurry form arranged on the mesh is heated and dried to obtain a liquid crystal polymer fiber mat.
[0087] (Hot pressing process: S23) Next, in the hot pressing step, the liquid crystal polymer fiber mat is hot pressed to obtain a liquid crystal polymer film. Specifically, in the hot pressing step, the liquid crystal polymer fiber mat is hot pressed together with copper foil. This allows the hot pressing step to also serve as a step of bonding the liquid crystal polymer film and the copper foil to each other, so that a liquid crystal polymer film with the copper foil bonded thereto can be obtained at low cost. In addition, when heating is performed for a long time in the hot pressing step, it is preferable to vacuum hot press the liquid crystal polymer fiber mat. Furthermore, in the hot pressing step, a preliminary press may be performed at a temperature of 220°C or less before performing the vacuum hot pressing. By performing the preliminary press, the density of the fiber mat can be increased, and the coefficient of linear expansion (CTE) of the liquid crystal polymer film can be reduced. The density of the fiber mat is preferably 0.1 to 1.5 g / cm. 3 and more preferably 0.3 to 1.4 g / cm 3 It is.
[0088] In the hot pressing step, the hot pressing is preferably performed at a temperature about 5°C to 15°C lower than the melting point of the liquid crystal polymer (raw material) constituting the liquid crystal polymer powder. If the hot pressing is performed at a temperature about 5°C to 15°C lower than the endothermic peak temperature, the sintering of the liquid crystal polymers is facilitated.
[0089] In addition, in the hot pressing process, a release film such as a polyimide film, a PTFE film, or a composite sheet made of a reinforcing material such as a glass fiber fabric and a heat-resistant resin may be sandwiched between the press used in the hot pressing process and the liquid crystal polymer fiber mat.
[0090] Alternatively, instead of the polyimide film, an additional copper foil may be sandwiched between the press and the liquid crystal polymer fiber mat. In this case, a liquid crystal polymer film having copper foil bonded to both sides can be obtained. The liquid crystal polymer film having copper foil bonded to both sides can be used as a double-sided copper-clad FCCL.
[0091] The outer dimensions of the liquid crystal polymer film formed by the hot pressing process in the thickness direction, i.e., the planar dimensions along the film surface, are approximately the same as those of the liquid crystal polymer fiber mat before the hot pressing. Then, by the hot pressing, the fibrous particles of the liquid crystal polymer powder in the liquid crystal polymer fiber mat, which have a longitudinal direction along the thickness direction of the liquid crystal polymer fiber mat, are heated while being pressed down in the in-plane direction of the copper foil. Since the liquid crystal polymer constituting the liquid crystal polymer powder has a molecular axial direction in the longitudinal direction of the fibrous particles, the axial direction of the liquid crystal polymer molecules is also pressed down in the in-plane direction of the copper foil. Therefore, except for the molecules constituting the clumped particles, the axial direction of each of the molecules constituting the liquid crystal polymer is oriented along the in-plane direction of the liquid crystal polymer film across the thickness direction of the liquid crystal polymer film. Therefore, in the formed liquid crystal polymer film, the main orientation direction of the liquid crystal polymer molecules tends to be along the in-plane direction of the copper foil, i.e., the in-plane direction of the liquid crystal polymer film.
[0092] It is believed that this is the reason why the in-plane linear expansion coefficient of the liquid crystal polymer film of this embodiment is reduced. Note that a liquid crystal polymer film having a low in-plane linear expansion coefficient has the advantage of being excellent in dimensional stability. In addition, when copper foil is laminated to the liquid crystal polymer film, it is possible to reduce the linear expansion coefficient of the liquid crystal polymer film to be approximately the same as the linear expansion coefficient of the copper foil (about 18 to 20 ppm / ° C.), which can suppress defects such as warping due to thermal shrinkage in the liquid crystal polymer film laminated with the copper foil.
[0093] Furthermore, the liquid crystal polymer powder in the liquid crystal polymer fiber mat may be bonded to each other while the fibrous particles remain entangled with each other. As a result, the liquid crystal polymer in the liquid crystal polymer film has a structure in which each molecule is entangled with each other. In addition, since the fibrous particles have a larger surface area than a spherical liquid crystal polymer having the same volume, the bonding area when the liquid crystal polymer powder is bonded to each other by the hot pressing process is also larger. As a result, the toughness and folding strength of the liquid crystal polymer film according to this embodiment are improved. In addition, the thickness of the liquid crystal polymer film is thinner than that of the liquid crystal polymer fiber mat by the hot pressing process.
[0094] In addition, the liquid crystal polymer mat obtained by matting the conventional liquid crystal polymer powder not containing the above-mentioned fibrous particles does not contain fibrous particles having the molecular axis direction in the longitudinal direction. Therefore, even if such a liquid crystal polymer mat is hot-pressed, the axial direction of the molecules constituting the liquid crystal polymer in the liquid crystal polymer film is not pushed down. Therefore, even if a liquid crystal polymer film is produced using a conventional liquid crystal polymer powder not containing fibrous particles, the main orientation direction of each of the molecules constituting the liquid crystal polymer does not follow the in-plane direction of the liquid crystal polymer film.
[0095] In addition, even if the liquid crystal polymer fiber mat obtained by matting the conventional liquid crystal polymer powder not containing fibrous particles is heat-pressed, the bonding area when the liquid crystal polymer powder particles are bonded to each other is extremely small. Therefore, when an external force is applied to a liquid crystal polymer film manufactured using a conventional liquid crystal polymer powder not containing fibrous particles, stress is concentrated at the bonding portion between the liquid crystal polymer powder particles. And, since the bonding area of the bonding portion is small, the liquid crystal polymer film is broken at the bonding portion when an external force is applied. Thus, the liquid crystal polymer film manufactured using a conventional liquid crystal polymer powder not containing fibrous particles has a weak strength, and has low toughness and folding strength. The liquid crystal polymer film cannot be used as a substrate, a diaphragm, or a vibration damping plate for an FPC.
[0096] (Metal foil removal process: S24) Finally, if necessary, the metal foil bonded to the liquid crystal polymer film may be removed by etching, etc. This provides a liquid crystal polymer film free of the metal foil.
[0097] According to the manufacturing method of the liquid crystal polymer film of this embodiment, a liquid crystal polymer film can be manufactured using a liquid crystal polymer powder containing fibrous particles having an average aspect ratio of 10 or more and 500 or less and an average diameter of 2 μm or less, which was not possible to achieve in the past, thereby obtaining a liquid crystal polymer film with excellent folding strength, etc., which can be suitably used as a circuit board.
[0098] Conventionally, LCP films have been produced by melt extrusion, solution casting, and the like. In the case of the melt extrusion method, it was necessary to use an LCP with a relatively low melting point that can be melted in the production equipment. In addition, in the case of the solution casting method, it was necessary to use an LCP having an amide bond that can be dispersed in a solvent. In contrast, in the production method of the LCP film of the present embodiment, since it is not necessary to melt the LCP, it is not limited to the above-mentioned LCP with a low melting point or LCP that can be dispersed in a solvent, and other LCPs can be used. Therefore, for example, a liquid crystal polymer with a melting point of more than 330°C can be adopted, and a liquid crystal polymer film with excellent heat resistance containing a liquid crystal polymer with a melting point of more than 330°C can be produced.
[0099] <Method of manufacturing fiber mat> 14, the method for producing a fiber mat according to this embodiment includes a dispersion step (S31) and a mat-forming step (S32). The dispersion step (S31) is the same as the dispersion step (S21) in the method for producing a liquid crystal polymer film.
[0100] In the mat-forming step (S32), the liquid crystal polymer powder slurry is formed into a liquid crystal polymer fiber mat by a papermaking method. In the papermaking method, the dispersion medium used in the dispersion step can be recovered and reused, and the fiber mat can be produced at low cost.
[0101] 15 is a diagram showing an example of a matting step for matting the liquid crystal polymer powder in the manufacturing process of the fiber mat. With reference to FIG. 15, the matting step will be described in detail.
[0102] 15, the mat-forming step uses a papermaking machine 100. The papermaking machine 100 includes a supply roller 15 that supplies the microporous sheet 10, a take-up roller (not shown) that collects the microporous sheet 10, a papermaking wire 20, transport rollers 25 and 26, a storage section 40 that stores a dispersion medium 41 in which the liquid crystalline polymer powder is dispersed, a heating device 50, and a light irradiation device 60.
[0103] The papermaking wire 20 is, for example, a papermaking mesh of about 80 to 100 mesh. That is, the papermaking wire 20 has a pore size of about 150 μm to 180 μm. The papermaking wire 20 is transported by transport rollers 25 and 26 arranged in the transport direction. The transport roller 26 is disposed downstream of the transport roller 26. The papermaking wire 20 is transported by the transport rollers 25 and 26 so as to pass through the storage section 40.
[0104] The supply roller 15 supplies the microporous sheet 10 onto the papermaking wire 20. The microporous sheet 10 functions as a support for supporting the liquid crystalline polymer powder. The microporous sheet 10 placed on the papermaking wire 20 is transported by the papermaking wire 20 to pass through the storage section 40. The microporous sheet 10 that has passed through the storage section 40 is peeled off from the papermaking wire 20 and taken up by a take-up roller.
[0105] The microporous sheet 10 has a finer mesh than the papermaking wire 20. The microporous sheet 10 preferably has a mesh size of approximately 157 or more. In other words, the microporous sheet 10 preferably has a pore size of approximately 100 μm or less. This makes it possible to collect the fine liquid crystal polymer powder dispersed in the dispersion medium.
[0106] More preferably, the microporous sheet 10 has a pore size of about 5 μm to 50 μm. If the pore size of the microporous sheet 10 is too small, the drainage is poor and the time required for dehydration is long. On the other hand, if the pore size of the microporous sheet 10 is too large, it is difficult to collect the fine fibers (fine liquid crystal polymer powder), resulting in a poor yield.
[0107] When a microporous sheet 10 having a variation in pore size is selected, the texture of the formed fiber mat is affected, so when high uniformity is required for the fiber mat, a mesh that is periodically woven in a reticulated pattern is preferred. In other words, it is preferable to use a mesh for the microporous sheet 10 in which the pore size is uniform and the pores are not distributed unevenly.
[0108] For example, a woven mesh having a pore size of 50 μm or less can be used as the microporous sheet 10. As the woven mesh, for example, one made of synthetic fibers such as polyester can be used.
[0109] The microporous sheet 10 may have a basis weight of 15 g / m. 2 The following wet-laid nonwoven fabrics may be used. As the wet-laid nonwoven fabric, one made of microfibers may be used. The microfibers are made of synthetic fibers such as polyester.
[0110] The heating device 50 is disposed downstream of the storage section 40 in the conveying direction. The heating device 50 heats and dries the liquid crystal polymer powder 30 that has been woven onto the microporous sheet 10. As a result, a fiber mat is formed on the microporous sheet 10.
[0111] The light irradiation device 60 is disposed downstream of the heating device 50 in the conveying direction. The light irradiation device 60 irradiates light toward the fiber mat formed on the microporous sheet 10. The light irradiation device 60 may be, for example, a flash lamp.
[0112] The light irradiation device 60 preferably irradiates pulsed light. Since the pulsed light is absorbed by the surface (first main surface 31) of the fiber mat, the support (microporous sheet 10) supporting the fiber mat is not deteriorated by light irradiation. Therefore, a material having a lower melting point than the fiber mat can be used as the support, and the range of support options is expanded. In addition, since the fiber mat can be prevented from fusing to the support, the support can be reused repeatedly. As the light irradiation device 60, a light irradiation device (PulseForge (registered trademark) 1300 manufactured by NovaCentrix) can be used.
[0113] The mat-forming step (S32) includes a paper-making step, a peeling step, and a drying step, and may further include a light irradiation step. In the mat-forming step (S32), first, in a paper-making step, the dispersed liquid crystal polymer powder is papered into a microporous sheet 10. Specifically, the microporous sheet 10 supplied onto a papermaking wire 20 is conveyed by the papermaking wire 20 and passed through a storage section 40. At this time, the liquid crystal polymer powder dispersed in the dispersion medium 41 stored in the storage section 40 is papered into the microporous sheet 10.
[0114] Next, in a peeling step, the microporous sheet formed by weaving up the dispersed liquid crystal polymer powder is peeled off from the papermaking wire 20. Specifically, the microporous sheet 10 is wound up by a winding roller, thereby transporting the microporous sheet 10 in a direction different from that of the papermaking wire 20. The papermaking wire 20 may be transported in a direction different from that of the microporous sheet 10 by a transport roller 26.
[0115] Next, in a drying step, the liquid crystal polymer powder laid on the microporous sheet 10 is heated and dried by a heater 50. As a result, a fiber mat 30 made of the liquid crystal polymer is formed on the microporous sheet 10.
[0116] Next, in the light irradiation step, the first main surface 31 of the fiber mat 30 located on the opposite side to the side on which the microporous sheet 10 is located is irradiated with light. This causes the liquid crystal polymer powder located on the first main surface 31 side to fuse together. As a result, the strength of the fiber mat 30 is improved, and the fiber mat 30 can be carried to the next step without being damaged.
[0117] Furthermore, since only the liquid crystal polymer powder located in the surface layer on the first main surface 31 side is fused, the density of the entire fiber mat 30 is low, which makes it possible to ensure high breathability and high collection efficiency.
[0118] The fiber mat 30 after the light irradiation is placed on the microporous sheet 10 and then wound up by the winding roller in the winding process.
[0119] Fig. 16 is a diagram showing a step of irradiating the second surface of the fiber mat with light. As shown in Fig. 16, the mat-forming step may further include a step of peeling the fiber mat 30, the first main surface 31 of which has been irradiated with light, from the microporous sheet 10, and irradiating the second main surface 32 of the fiber mat 30 located on the opposite side to the side where the first main surface 31 is located with light. In this step, the fine fibers located on the second main surface 32 side are fused by light irradiation from a light irradiation device 61. The light irradiation device 61 may be the same as the light irradiation device 60 described above. When irradiating with light, the fiber mat 30 is irradiated while being transported.
[0120] When the liquid crystal polymer powder is fused on both the first main surface 31 side and the second main surface 32 side, the strength of the fiber mat 30 can be further improved.
[0121] Furthermore, when the fiber mat 30 is peeled off from the microporous sheet 10, since the liquid crystal polymer powder is fused on the first main surface 31 side and the fiber mat 30 has sufficient strength, the fiber mat 30 can be peeled off without damaging the fiber mat 30. The fiber mat 30 thus produced may be used as it is, or may be subjected to the hot pressing step S23 in the manufacturing method of a liquid crystal polymer film.
[0122] In this embodiment, light is irradiated to the fiber mat 30. When the liquid crystal polymer powder contained in the fiber mat contains a zirconium compound, the light absorption characteristics of the zirconium compound may increase the light irradiation efficiency. The increased light irradiation efficiency may improve the breaking tension of the fiber mat.
[0123] <<Method of processing liquid crystal polymer film and fiber mat>> In this embodiment, a liquid crystal polymer film and a fiber mat are irradiated with a laser to form a through hole or a cut portion. For the laser irradiation, a commercially available laser processing machine using, for example, a CO2 or semiconductor laser oscillator can be used. The beam spot diameter of the laser light can be changed by changing the lens of the laser processing machine. For fine processing, a small beam spot diameter is preferable.
[0124] When the liquid crystal polymer film or fiber mat contains a zirconium compound, the efficiency of laser irradiation is improved, making it easier to form through holes. EXAMPLES
[0125] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.
[0126] <Example 1> (Production of Liquid Crystal Polymer Pellets) In Example 1, first, uniaxially oriented liquid crystal polymer pellets were produced as LCP pellets. Specifically, the pellets were produced by melt extrusion under the following conditions.
[0127] The liquid crystal polymer raw material used to manufacture the LCP pellets had a melting point of 320°C and a melt viscosity (MV) of 32 Pa·s. The liquid crystal polymer raw material was a copolymer of HBA (p-hydroxybenzoic acid) and HNA (4-hydroxy-2-naphthoic acid). Prior to the melt-kneading process, the powder of the LCP raw material was dried at 150°C for 2 hours to prevent the incorporation of moisture.
[0128] The melt-kneading step and the extrusion step were carried out using a co-rotating twin screw extruder "HK-25D" (manufactured by Parker Corporation). The screw of the extruder had a diameter D of 25 mm, and L (length) / D was 41. The nozzle of the extruder was a single-hole nozzle with a diameter of 5 mm.
[0129] In the melt-kneading process and the extrusion process, first, the LCP raw material powder or pellets were fed from a hopper to the extruder. The LCP raw material was fed at a rate of 2 kg / h. A constant amount of LCP raw material was fed using a gravimetric lightweight single-axis feeder "K-CL-SFS-KQx4" (manufactured by Coperion Co., Ltd.).
[0130] In the above-mentioned co-rotating twin screw extruder, the supplied LCP raw material was melt-kneaded by the screws, and a string-like LCP was extruded from the nozzle. The screw rotation speed was 200 rpm, and the melt extrusion temperature (the temperature at which the molten LCP raw material was extruded from the nozzle hole) was 320°C. Here, the extrusion rate (Q) of the string-like material was basically the same as the supply rate of the LCP raw material, 2 kg / h.
[0131] Next, in the cooling step, the strand obtained in the extrusion step was passed through water while being taken up, thereby cooling the strand in water. The take-up speed (V) of the strand was set to 39.3 m / min. The ratio (V / Q) of the take-up speed (V) to the extrusion amount (Q) was approximately 19.6. The horizontal distance over which the strand was immersed in water was set to 105 cm.
[0132] Next, in the cutting process, the string-like material after the cooling process was cut to obtain trapezoidal columnar LCP pellets. The size of the trapezoidal column was 2 mm at the top, 3 mm at the bottom, 1 mm in height (thickness), and 4 mm in length.
[0133] (Production of liquid crystal polymer powder) The LCP pellets obtained above were coarsely pulverized using a cutter mill (MF10, manufactured by IKA). The coarsely pulverized liquid crystal polymer was passed through a 3 mm mesh provided at the outlet of the cutter mill to obtain a coarsely pulverized liquid crystal polymer.
[0134] Next, the coarsely pulverized liquid crystal polymer was finely pulverized in a liquid nitrogen bead mill (LNM-08, manufactured by IMEX, vessel capacity: 0.8 L). Specifically, 400 mL of media and 30 g of the coarsely pulverized liquid crystal polymer were put into a vessel, and pulverization was performed for 120 minutes at a rotation speed of 2000 rpm (disk peripheral speed: 5.2 m / s). Zirconia (ZrO2) beads with a diameter of 5 mm were used as the media. In the liquid nitrogen bead mill, the coarsely pulverized liquid crystal polymer was dispersed in liquid nitrogen, and the wet pulverization was performed. In this way, the coarsely pulverized liquid crystal polymer was pulverized in the liquid nitrogen bead mill to obtain a granular finely pulverized liquid crystal polymer.
[0135] The particle size of the finely pulverized liquid crystal polymer was measured. In the particle size measurement, the finely pulverized liquid crystal polymer dispersed in the dispersion medium was subjected to ultrasonic treatment for 10 seconds, and then set in a particle size distribution measuring device (LA-950, manufactured by Horiba, Ltd.) using the laser diffraction scattering method, and the particle size was measured. Ethanol was used as the dispersion medium.
[0136] Next, the dispersion liquid obtained by dispersing the finely pulverized liquid crystal polymer in ethanol was sieved through a mesh with an opening of 100 μm to remove coarse particles contained in the finely pulverized liquid crystal polymer, and the finely pulverized liquid crystal polymer that passed through the mesh was collected. The yield of the finely pulverized liquid crystal polymer after removing the coarse particles was 75% by mass.
[0137] Next, the finely pulverized liquid crystal polymer from which the coarse particles had been removed was dispersed in a 20% by mass ethanol aqueous solution. The ethanol slurry in which the finely pulverized liquid crystal polymer was dispersed was repeatedly crushed five times using a wet high-pressure crushing device under conditions of a slit chamber nozzle diameter of 0.2 mm and a pressure of 200 MPa, to form fibers. As the wet high-pressure crushing device, a high-pressure disperser (Nano-Veita manufactured by Yoshida Kikai Kogyo Co., Ltd.) was used. As a result, a liquid crystal polymer powder in a state of being dispersed in an ethanol aqueous solution was obtained.
[0138] (Production of liquid crystal polymer films) First, a paste of the liquid crystal polymer powder was applied onto a copper foil and dried to form a liquid crystal polymer web (liquid crystal polymer fiber mat) on the copper foil.
[0139] Specifically, terpineol was added to the ethanol aqueous solution in which the liquid crystal polymer powder was dispersed, in an amount 20 times the mass of the dispersed liquid crystal polymer powder. The aqueous solution was then heated while being stirred, and the water and ethanol were evaporated and removed. This resulted in the liquid crystal polymer powder dispersed in terpineol. That is, the liquid crystal polymer powder was dispersed in terpineol, which is a dispersion medium, to form a paste.
[0140] Next, the liquid crystal polymer paste was applied onto the roughened surface of an electrolytic copper foil (FWJ-WS-12, manufactured by Furukawa Electric Co., Ltd.) having a thickness of 12 μm. The electrolytic copper foil on which the liquid crystal polymer paste powder was applied was heated to 130° C. on a hot plate to vaporize the terpineol, which was the dispersion medium, and dry the liquid crystal polymer paste powder on the electrolytic copper foil. In this way, a thin liquid crystal polymer fiber mat was formed on the electrolytic copper foil.
[0141] The liquid crystal polymer powder paste was further applied onto this thin liquid crystal polymer fiber mat. The applied liquid crystal polymer powder paste was dried in the same manner as the previously applied liquid crystal polymer paste was dried. By repeating the above application and drying several times, the basis weight was increased to 35 g / m. 2 A liquid crystal polymer fiber mat adjusted to have the above structure was formed on an electrolytic copper foil.
[0142] Next, the liquid crystal polymer fiber mat formed on the electrolytic copper foil was hot-pressed together with the electrolytic copper foil using a vacuum hot press device (Kitagawa Seiki Co., Ltd., KVHC). Specifically, a release film was first laminated on the liquid crystal polymer fiber mat formed on the electrolytic copper foil on the side opposite to the electrolytic copper foil side. As the release film, a polyimide film (Toray DuPont Co., Ltd., Kapton (registered trademark) 100H) was used. Then, the liquid crystal polymer fiber mat laminated with the release film was set in the vacuum hot press device at room temperature. The set liquid crystal polymer fiber mat was pressed together with the release film and the electrolytic copper foil at a press pressure of 0.2 MPa, while increasing the temperature to 305°C at a rate of 7°C / min. After reaching 305°C, the liquid crystal polymer film was pressed together with the release film and the electrolytic copper foil at a press pressure of 6 MPa for 5 minutes while maintaining the temperature at 305°C. The press size (the length of one side of the square liquid crystal polymer fiber mat) was 170 mm. After the hot pressing, the release film was removed to obtain a liquid crystal polymer film formed on the electrolytic copper foil.
[0143] Finally, the electrolytic copper foil that had been bonded to the liquid crystal polymer film was removed by etching with an aqueous solution of ferric chloride. This resulted in the production of a liquid crystal polymer film. The thickness of the liquid crystal polymer film was 25 μm.
[0144] <Example 2> In Example 2, the supply amount of the LCP raw material (extruding amount of the string-like material) was 3 kg / h, and the take-up speed was 42.3 m / min. Except for this, LCP pellets and LCP powder were produced in the same manner as in Example 1, and an LCP film was obtained.
[0145] <Example 3> In Example 3, an LCP raw material (a copolymer of HBA (p-hydroxybenzoic acid) and HNA (4-hydroxy-2-naphthoic acid)) with an MV of 33 (melting point of 320°C) was used. The supply amount of the LCP raw material (extruding amount of string-like material) was 4 kg / h, and the take-up speed was 26.3 m / min. In other respects, LCP pellets and LCP powder were produced in the same manner as in Example 2, and an LCP film was obtained.
[0146] <Example 4> In Example 4, an LCP raw material (a copolymer of HBA (p-hydroxybenzoic acid) and HNA (4-hydroxy-2-naphthoic acid)) with an MV of 32 (melting point of 320°C) was used. The take-up speed was 20.3 m / min. Except for this, LCP pellets and LCP powder were produced in the same manner as in Example 3, and an LCP film was obtained.
[0147] <Comparative Example 1> In Comparative Example 1, the supply rate of the LCP raw material (extruding rate of the string-like material) was 8 kg / h. Except for this, LCP pellets and LCP powder were produced in the same manner as in Example 2, and an LCP film was obtained. The shape of the LCP pellets in Comparative Example 1 was close to an elliptical cylinder with a major axis of 4 mm, a minor axis of 1 mm, and a length of 4 mm.
[0148] <Comparative Example 2> In Comparative Example 2, the supply amount of the LCP raw material (the amount of the string-like material extruded) was 8 kg / h. Except for this, LCP pellets and LCP powder were produced in the same manner as in Example 3, and an LCP film was obtained.
[0149] [Observation of liquid crystal polymer pellets] Observations were carried out on the liquid crystal polymer pellets in Example 1, Comparative Example 1, Comparative Example 2, Example 2, Example 3, and Example 4. Figs. 3 to 8 are photographs of the liquid crystal polymer pellets in Example 1, Comparative Example 1, Comparative Example 2, Example 2, Example 3, and Example 4, respectively. The photographs were taken at a magnification of 20 times using a digital microscope (VHX-5000) manufactured by Keyence Corporation. From the photographs in Figs. 3 to 8, it can be seen that the LCP pellets in the examples have larger fibrous branching portions such as burrs and fluff than the LCP pellets in the comparative examples.
[0150] [Measurement of the degree of orientation of liquid crystal polymer pellets] The orientation degree of the liquid crystal polymer pellets according to each of the examples and comparative examples was measured by wide-angle X-ray scattering (WAXS). Specifically, the WAXS analysis was performed using a wide-angle measurement mode of a small-angle X-ray scattering analyzer (Rigaku's "NANOPIX"). The distance between the liquid crystal polymer pellet sample and the detector was 80 mm, and the distance was calibrated using Si. The sample was irradiated with X-rays and the scattered X-rays were detected by the detector in a vacuum environment. A beam stopper was placed between the sample and the detector to block some of the scattered X-rays from reaching the detector. The degree of orientation was calculated from the circular integral at the strongest peak of the scattering intensity of the scattered X-rays.
[0151] [Measurement of compacted bulk density of liquid crystal polymer pellets] The packed bulk density of the liquid crystal polymer pellets according to each of the examples and the comparative examples was measured. Specifically, first, LCP pellets were filled into a measuring cylinder (maximum scale: 100 mL) up to the 100 mL mark, and the weight of the filled LCP pellets was measured. Then, tapping (up and down vibration of the measuring cylinder) was performed 10 times, and the volume of the LCP pellets after tapping was confirmed by the scale of the measuring cylinder. The packed bulk density was calculated from the following formula. Packed bulk density (g / cm 3 ) = [Weight of filled LCP pellets (g)] / [Volume of LCP pellets after tapping (cm 3 )〕 The measurement results of the packed bulk density of the liquid crystal polymer pellets are shown in Table 1 and FIG.
[0152] [Measurement of linear expansion coefficient] The in-plane linear expansion coefficient was measured for each of the liquid crystal polymer films according to the examples and comparative examples. Specifically, the in-plane (XY direction) linear expansion coefficient was measured for the liquid crystal polymer film by a TMA (thermo-mechanical analysis) method in accordance with JIS K 7197. The TMA conditions were that the temperature was increased from room temperature to 150°C at a rate of 10°C / min under a nitrogen atmosphere, the load was 10g, and the sample shape was a strip (5mm x 15mm). The measurement results of the coefficient of linear expansion (CTE) of the liquid crystal polymer film are shown in Table 1 and FIG.
[0153] [Table 1]
[0154] From the results shown in Table 1 and Figure 1, it can be seen that in the LCP pellet manufacturing process, in the examples where the ratio (V / Q) of the take-up speed (V) to the extrusion amount (Q) of the string-like material is 5 or more, LCP pellets with an orientation degree of 86% or more can be obtained. In contrast, in the comparative examples where V / Q is less than 5, the orientation degree of the LCP pellets was less than 86%. This is thought to be because by making V / Q 5 or more, the stretching ratio becomes large, making it easier for the liquid crystal molecules to align in the same direction.
[0155] Furthermore, the liquid crystal polymer films of Examples 1 to 4, which were prepared using liquid crystal polymer pellets with an orientation degree of 86% or more, had a CTE of 20 ppm / °C or less, which is smaller than the CTE of the liquid crystal polymer films of Comparative Examples 1 and 2, which were prepared using liquid crystal polymer pellets with an orientation degree of less than 86%.
[0156] By increasing the degree of orientation of the LCP during the LCP pellet production process, the finely pulverized LCP pellets are pulverized to produce particles that retain the highly oriented state that is inherent to the pellets. By processing these particles in a wet high-pressure crushing device, LCP powder containing fibrous particles of liquid crystal polymer that maintain a highly oriented state can be obtained. In general, in liquid crystal polymers, the LCP bonds perpendicular to the molecular chain arrangement are more likely to break than the LCP bonds in the molecular chain direction. Therefore, the fibrous particles contained in the produced LCP powder tend to be long in the orientation direction and short in the direction perpendicular to the orientation. In addition, liquid crystal polymers have a negative coefficient of thermal expansion in the direction in which the molecules are oriented, so when such LCP powder is used to produce an LCP film, it is possible to obtain an LCP film with a small in-plane (planar) linear expansion coefficient (coefficient of thermal expansion).
[0157] Furthermore, from the results shown in Table 1 and Figure 2, it can be seen that as the orientation degree of the liquid crystal polymer pellets increases, the packed bulk density of the liquid crystal polymer pellets decreases. This is thought to be because as the orientation degree of the liquid crystal polymer pellets increases, the molecules are aligned and the pellets become more fibrous, which causes larger voids due to burrs, fuzz, and other fibrous branching portions that occur during cutting.
[0158] Furthermore, by producing a liquid crystal polymer film using liquid crystal polymer pellets with a high degree of orientation and bulk density, a liquid crystal polymer film composed of highly oriented fine fibers (fibrous particles) is formed, and it is believed that the in-plane CTE of the liquid crystal polymer film is reduced.
[0159] <Reference Test 1> Except for changing the take-off speed to 4.6 m / min and 46.3 m / min, an LCP powder and an LCP film were produced in the same manner as in Example 2. The packed bulk density of the LCP pellets, the degree of orientation of the LCP pellets, and the CTE of the LCP film were measured in the same manner as above. Figure 12 shows the relationship between the take-up speed (m / min) and the compacted bulk density (g / cm) of the LCP pellets when the take-up speed (draw ratio) was changed in this way. 3 ), the degree of orientation (%) of the LCP pellets, and the CTE (ppm / °C) of the LCP film.
[0160] From the results shown in Figure 12, it can be seen that increasing the draw ratio (take-off speed) increases the degree of orientation of the LCP pellets and decreases the packed bulk density of the LCP pellets, which in turn decreases the CTE of the LCP film. If the draw ratio is too low, the supply of LCP raw material will exceed the recovery (take-up) amount of the strands, and pellets may not be produced. If the draw ratio is too high, the strands may be cut when taken up, and pellets may not be produced.
[0161] <Reference Test 2> An LCP powder and an LCP film were prepared in the same manner as in Example 2, except that the melt extrusion temperature was changed to 310° C., 320° C., and 330° C. The packed bulk density of the LCP pellets, the degree of orientation of the LCP pellets, and the CTE of the LCP film were measured in the same manner as above. FIG. 13 shows the relationship between the melt extrusion temperature (°C) and the compacted bulk density (g / cm) of the LCP pellets when the melt extrusion temperature was changed in this way. 3 ), the degree of orientation (%) of the LCP pellets, and the CTE (ppm / °C) of the LCP film.
[0162] From the results shown in Figure 13, it can be seen that when the melt extrusion temperature is equal to or higher than the melting point of the LCP raw material, the orientation degree of the LCP pellets increases and the packed bulk density of the LCP pellets decreases, which in turn reduces the CTE of the LCP film. This is believed to be because when the melt extrusion temperature is equal to or higher than the melting point of the LCP raw material, the fluidity of the LCP increases, making it easier for the molecules to align when the LCP is extruded from the nozzle holes of the extruder. If the melt extrusion temperature is increased too much, the decomposition temperature of the resin will be exceeded, making it difficult to produce LCP pellets.
[0163] <Example 5> A liquid crystal polymer film of Example 5 was produced using the same raw materials as in Example 4. The only difference from Example 4 is that a preliminary pressing process was performed as a process before the liquid crystal polymer fiber mat formed on the electrolytic copper foil was hot-pressed together with the electrolytic copper foil using a vacuum high-temperature press device. The preliminary pressing process first performed pressing at room temperature (7 MPa, 10 sec), and then pressing at 200°C (7 MPa, 10 sec). Thereafter, the same treatment as in Example 4 was performed, specifically, a heat treatment was performed using a vacuum high-temperature press device (Kitagawa Seiki Co., Ltd., KVHC).
[0164] (evaluation) The density of the fiber mats of Examples 4 and 5 was measured by the following method. The coefficient of linear expansion (CTE) of the liquid crystal polymer film of Example 5 was measured by the same method as that of the liquid crystal polymer film of Example 4. The measurement results are shown in Table 2.
[0165] (Measurement of density of fiber mat) The density of the fiber mat was calculated by measuring the weight and thickness of the liquid crystal polymer fiber mat formed on the electrolytic copper foil. Specifically, the weight of the liquid crystal polymer fiber mat was calculated by subtracting the weight of the electrolytic copper foil from the measured weight. The thickness was measured using a micro gauge.
[0166] [Table 2]
[0167] From the results shown in Table 2, it can be seen that the density of the fiber mat is increased by performing the preliminary pressing, and the coefficient of linear expansion (CTE) of the liquid crystal polymer film is reduced. By the preliminary pressing, among the fibrous particles of the liquid crystal polymer powder in the fiber mat, the fibrous particles having a longitudinal direction along the thickness direction of the liquid crystal polymer fiber mat are pushed down in the in-plane direction of the copper foil. Therefore, except for the molecules constituting the clumped particles, the axial direction of each of the molecules constituting the liquid crystal polymer is oriented along the in-plane direction of the liquid crystal polymer film across the thickness direction of the liquid crystal polymer film. Therefore, in the molded liquid crystal polymer film, the main orientation direction of the molecules of the liquid crystal polymer tends to be along the in-plane direction of the copper foil, that is, the in-plane direction of the liquid crystal polymer film. As a result, the CTE of the liquid crystal polymer film of this embodiment is reduced, and in the liquid crystal polymer film to which the copper foil is laminated, defects such as warping due to thermal shrinkage can be suppressed.
[0168] <Example 6, Comparative Example 2> (Production of fiber mats of Example 6 and Comparative Example 2) Using the liquid crystal polymer powder of Example 4 (melting point 320°C), the necessary amount of water and ethanol were added to prepare 2.2g of liquid crystal polymer powder per 30L of 50wt% ethanol aqueous solution, and the slurry liquid crystal polymer powder was formed into a fiber mat by a papermaking method. A square sheet machine 2555 manufactured by Kumagai Riki Co., Ltd. was used as the papermaking machine, and the liquid crystal polymer powder dispersed in the dispersion medium was papered on a microporous sheet of polyester mesh with a pore size of 11μm. Next, the fiber mat of Example 6 was formed on the microporous sheet by heating and drying at a temperature of 100°C using a hot air dryer. The basis weight of the fiber mat was 35g / m 2 That was about it.
[0169] The obtained fiber mat was peeled off from the microporous sheet and heat-treated in a N2 atmosphere for 1 hour at temperatures of 280°C, 320°C, and 360°C. An inert oven was used as the heating furnace.
[0170] The fiber mat of Comparative Example 2 was prepared in the same manner as the fiber mat of Example 6 using the liquid crystal polymer powder of Comparative Example 1 (melting point 320°C), and was subjected to heat treatment at temperatures of 280°C, 320°C, and 360°C in the same manner as the fiber mat of Example 6. The breaking tension of the fiber mats of Example 6 and Comparative Example 2 was measured by the following method. The measurement results are shown in Table 3.
[0171] (Measurement of breaking tension of fiber mat) The breaking tension was measured for the fiber mats of Example 6 and Comparative Example 2 that were heat-treated at each temperature. The breaking tension was measured using an autograph (AG-XDplus manufactured by Shimadzu Corporation) after processing the fiber mat after heat treatment into a width of 20 mm and a length of 100 mm. The measurement conditions were a take-up speed of 0.33 mm / sec, mode: tension, and an initial length of 50 mm.
[0172] [Table 3]
[0173] From the results shown in Table 3, it was found that in Example 6, even if the heat treatment temperature was 280° C., which was below the melting point, a breaking tension of 1.0 N / 20 mm or more was obtained.
[0174] <Examples 7 and 8> (Production of fiber mats of Examples 7 and 8) When the content of zirconia in the total amount of the liquid crystal polymer powder is W (wt%), the content of zirconia W of the liquid crystal polymer powder of Example 4 was 0.0219 wt%. The content of zirconia W was calculated by the following method. When the liquid crystal polymer powder of Example 4 was subjected to a process for removing zirconia by the following method, the content of zirconia W calculated by the following method was 0.0005 wt%.
[0175] Using the liquid crystal polymer powder of Example 4 (without zirconia removal treatment, with zirconia removal treatment), fiber mats of Example 7 (prepared using liquid crystal polymer powder without zirconia removal treatment) and Example 8 (prepared using liquid crystal polymer powder with zirconia removal treatment) were prepared in the same manner as in Example 6. Instead of the heat treatment in Example 6, a light irradiation treatment was performed on the entire surface of the fiber mat using a light irradiation device (NovaCentrix, PulseForge (registered trademark) 1300) with a set voltage of 230V, 250V, and 270V for 3.5msec with a table height of 10mm.
[0176] (Method for measuring residual zirconia amount) 40 g of the liquid crystal polymer powder to be measured was dispersed in 500 mL of 1 mol% aqua regia and allowed to stand for 10 minutes. The powder and solution were separated by suction filtration. The filtered solution was measured using an ICP optical emission spectrometer (ICPS-8100, Shimadzu Corporation) to confirm whether it could be detected above the detection limit. The standard solution for the calibration curve was prepared using ICP standard 1000 mg / L Ceriptur (Merck). Standard solutions for the calibration curve were prepared at 0, 0.25, 0.50, 1.0, and 2.0 mg / L. The measurement conditions for the ICP optical emission spectrometer were twin sequential type, high frequency output 1.2 kW, plasma gas flow rate 14 L / min, auxiliary gas flow rate 1.2 L / min, carrier gas flow rate 0.7 L / min, nebulizer coaxial type, and measurement direction horizontal. The detection limit was set to 0.02 μg / L or less. The zirconium content per weight of the liquid crystal polymer powder was calculated from the concentration of the ICP solution using the following formula, where the amount of Zr (molecular weight 91) was converted into the amount of ZrO2 (zirconia) (molecular weight 123). W (weight%) = (zirconium ion concentration of measured solution (g / L)) × (123 ÷ 91) × 0.5 L ÷ 40 g × 100
[0177] (Method of removing zirconium) 40 g of the liquid crystal polymer powder was dispersed in 500 mL of 1 mol% aqua regia and left to stand for 10 minutes. The powder and solution were separated by suction filtration, and the powder alone was dispersed in 500 mL of pure water. The dispersed powder was again separated by suction filtration. This process was repeated three times, and the mixture was heated to 100°C on a hot plate to evaporate the water, producing a liquid crystal polymer powder from which the zirconia had been removed.
[0178] (evaluation) (Measurement of breaking tension) After the light irradiation treatment, the breaking tension was measured by the above-mentioned method for the fiber mats of Examples 7 and 8. The measurement results are shown in Table 4.
[0179] [Table 4]
[0180] The results shown in Table 4 show that, compared with Example 8, Example 7 gave a fiber mat with a higher breaking tension.
[0181] (Laser processability) After light irradiation, the fiber mats of Examples 7 and 8 (with a set voltage for light irradiation treatment of 230 V) were irradiated with a laser under the following conditions to carry out laser processing. A KrF excimer laser with a wavelength of 248 nm was generated by a CoMPexPro series (manufactured by Coherent Corporation), and the generated laser was focused into an area of 1 mm square by a reflecting lens and a focusing lens. The prepared film was placed at the focal length for focusing, and the energy per irradiation (pulse) was 150 mJ / mm 2 The laser energy was set so that the energy was equal to 7 pulses. The laser processing was performed so that the fiber mat of Example 7 had a through hole, and the fiber mat of Example 8 could be cut, although no through hole was formed. From the above results, it was found that the fiber mat of Example 7, which did not undergo the zirconia removal treatment, could be laser processed more efficiently.
[0182] In the above description of the embodiments, configurations that can be combined may be combined with each other.
[0183] The embodiments and examples disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims.
[0184] <1> A liquid crystal polymer pellet containing a liquid crystal polymer and used as a material for a liquid crystal polymer film, Liquid crystal polymer pellets with a degree of orientation of 86% or more as measured by wide-angle X-ray scattering. <2> Compacted bulk density is 0.35g / cm 3 is less than <1> The liquid crystal polymer pellet according to claim 1. <3> having fibrous branches, <1> or <2> The liquid crystal polymer pellet according to claim 1. <4> A melt-kneading process in which a liquid crystal polymer raw material is kneaded while being heated and melted; an extrusion step of extruding the liquid crystal polymer raw material after the melt-kneading step into a string shape; a cooling step of cooling the string-like material obtained in the extrusion step in water while collecting it; A cutting step of cutting the string-like material after the cooling step, a ratio of the take-up speed (m / min) of the string-like material in the cooling step to the extrusion amount (kg / h) of the string-like material in the extrusion step is 5 to 20; The method for producing liquid crystal polymer pellets, wherein the melt extrusion temperature in the extrusion step is equal to or higher than the melting point of the liquid crystal polymer raw material. <5> <4> A liquid crystal polymer pellet obtained by the manufacturing method described in . <6> <1> ~ <3> and <5> a fine pulverization step of pulverizing the liquid crystal polymer pellets according to any one of the above while dispersed in liquid nitrogen to obtain a granular finely pulverized liquid crystal polymer; A fiberization step of crushing the finely pulverized liquid crystal polymer with a wet high-pressure crushing device to obtain a liquid crystal polymer powder; A method for producing a liquid crystal polymer powder comprising the steps of: <7> In the fine pulverization step, the liquid crystal polymer pellets dispersed in the liquid nitrogen are pulverized using media. <6> A method for producing the liquid crystal polymer powder according to claim 1. <8> <6> or <7> A liquid crystal polymer powder obtained by the production method described in 1. <9> When a fiber mat is formed using the liquid crystal polymer powder and heat-treated at a temperature below the melting point of the liquid crystal polymer powder, the fiber mat has a breaking tension of 1.0 N / 20 mm or more. <8> The liquid crystal polymer powder according to claim 1. <10> Further comprising a zirconium compound, <8> or <9> The liquid crystal polymer powder according to claim 1. <11> The zirconium compound is contained in an amount of 0.001% by weight or more and 0.1% by weight or less based on the total amount of the liquid crystal polymer powder. <10> The liquid crystal polymer powder according to claim 1. <12> A liquid crystal polymer film comprising a liquid crystal polymer, A liquid crystal polymer film having an in-plane linear expansion coefficient of 20 ppm / °C or less. <13> A fiber mat containing a liquid crystal polymer powder, the breaking tension of which is improved by heat treatment at a temperature below the melting point. <14> The density of the fiber mat is 0.1 to 1.5 g / cm 3 That is, <13> The fiber mat according to claim 1. <15> <8> ~ <11> A dispersing step of dispersing the liquid crystal polymer powder according to any one of the above in a dispersion medium to form a paste or a slurry; a matting step of drying the liquid crystal polymer powder in a paste or slurry form to form a liquid crystal polymer fiber mat; and a hot pressing step of hot pressing the liquid crystal polymer fiber mat to obtain a liquid crystal polymer film. <16> The mattification step includes a coating step of coating the liquid crystal polymer powder in a paste or slurry form on a copper foil. <15> 2. A method for producing a polymer film according to claim 1 . <17> In the hot pressing step, the liquid crystal polymer fiber mat is hot pressed together with the copper foil. <16> 2. A method for producing the liquid crystal polymer film according to claim 1 . <18> The process further includes a step of performing a pre-press at a temperature of 220 ° C. or less before the hot pressing step. <15> ~ <17> 13. A method for producing a liquid crystal polymer film according to claim 12. <19> In the mat-forming step, the liquid crystal polymer powder in a paste or slurry form is formed into the liquid crystal polymer fiber mat by a papermaking method; <15> ~ <18> 13. A method for producing a liquid crystal polymer film according to claim 12. <20> <15> ~ <19> 1. A liquid crystal polymer film obtained by the manufacturing method according to any one of the above. [Explanation of symbols]
[0185] 10 microporous sheet, 15 supply roller, 20 papermaking wire, 25, 26 transport rollers, 30 fiber mat, 31 first main surface, 32 second main surface, 40 storage section, 41 dispersion medium, 50 heating device, 60 light irradiation device, 100 papermaking machine.
Claims
1. A liquid crystal polymer pellet containing a liquid crystal polymer and used as a material for a liquid crystal polymer film, Liquid crystal polymer pellets having a degree of orientation of 86% or more as measured by wide angle X-ray scattering.
2. Compacted bulk density is 0.35 g / cm 3 2. The liquid crystalline polymer pellet according to claim 1, wherein:
3. The liquid crystal polymer pellet according to claim 1 or 2, which has fibrous branched portions.
Citation Information
Patent Citations
Output level stabilizing system
JP1984004307A
Manufacture of liquid crystal resin pellet
JP1998180753A
Method for manufacturing liquid crystalline resin pellet
JP2002018842A
Thermoplastic resin molded product and method for producing the same
JP2002241510A
Film for electronic circuit board and electronic circuit board
JP2016062955A